Synergistic damage behavior of He ion irradiation and molten salt corrosion in SiC at 750 °C - Jianfeng Zhang; Lin Zhao; Jinlei Yang; Qiantao Lei; Jun Lin; Ya Tang; Jianjian Li (Journal of Advanced Ceramics)
CVD SiC samples exposed to 400 keV He ion irradiation at 750 °C were subsequently corroded in FLiNaK molten salt at 750 °C for 166 h. After corrosion, the dissolution of Si led to the formation of a carbon-rich layer and obvious denudation of the SiC. The microstructure of the C-rich layer was first visualized and characterized via TEM, confirming that a graphitic structure was present inside the layer. Furthermore, the AFM images indicate that the denudation depth increases with increasing irradiation dose. Moreover, the Ni impurities in the salt play a key role in the irradiation-promoted corrosion of SiC. These findings suggest that Ni can preferentially react with irradiation-included homonuclear Si‒Si bonds to promote SiC corrosion. Moreover, the number density of He bubbles decreases as their size increases near or within the C-rich layer, and it is speculated that the vacancies created by the loss of Si result in the migration and coalescence of He bubbles. In conclusion, irradiation and corrosion at high temperatures induced synergistic damage behavior in SiC.